Physiology and Nutrition of Lampropedia hyalina - Puttlitz, Donald H. (1968)
A detailed study of the physiology and nutrition of Lampropedia hyalina revealed that it is an aerobic, cytochrome-containing chemoheterotroph which is limited in its energy sources to a few intermediates (and close derivatives) of the Krebs cycle. Reducing compounds at low levels are potent growth inhibitors. The microbe has no photosynthetic ability (despite its previous taxonomic position with the sulfur purple bacteria). The results of a general investigation of its physiology are reported. Added biotin and thiamine are needed for growth in defined media; pantothenate is strongly stimulatory. Alanine, arginine, and tyrosine, as well as NH(4)Cl, serve as sole nitrogen sources. A unique motion exhibited by cells of a rapidly growing culture is described. Aspects of its metabolism of poly-β-hydroxybutyrate and limiting aspects of its physiology as related to its ecology are discussed.